ZSF1 rat as animal model for HFpEF: Development of reduced diastolic function and skeletal muscle dysfunction. (25th July 2020) - Schauer, Antje; Draskowski, Runa; Jannasch, Anett; Kirchhoff, Virginia; Goto, Keita; Männel, Anita; Barthel, Peggy; Augstein, Antje; Winzer, Ephraim; Tugtekin, Malte; Labeit, Siegfried; Linke, Axel; et al.
Abstract: Aims: The prevalence of heart failure with preserved ejection fraction (HFpEF) is still increasing, and so far, no pharmaceutical treatment has proven to be effective. A key obstacle for testing new pharmaceutical substances is the availability of suitable animal models for HFpEF, which realistically reflect the clinical picture. The aim of the present study was to characterize the development of HFpEF and skeletal muscle (SM) dysfunction in ZSF1 rats over time. Methods and results: Echocardiography and functional analyses of the SM were performed in 6‐, 10‐, 15‐, 20‐, and 32‐week‐old ZSF1‐lean and ZSF1‐obese. Furthermore, myocardial and SM tissue was collected for molecular and histological analyses. HFpEF markers were evident as early as 10 weeks of age. Diastolic dysfunction, confirmed by a significant increase in E/e′, was detectable at 10 weeks. Increased left ventricular mRNA expression of collagen and BNP was detected in ZSF1‐obese animals as early as 15 and 20 weeks, respectively. The loss of muscle force was measurable in the extensor digitorum longus starting at 15 weeks, whereas the soleus muscle function was impaired at Week 32. In addition, at Week 20, markers for aortic valve sclerosis were increased. Conclusions: Our measurements confirmed the appearance of HFpEF in ZSF1‐obese rats as early as 10 weeks of age, most likely as a result of the pre‐existing co‐morbidities. In addition, SM function was reduced after the manifestation of HFpEF. In conclusion, the ZSF1 rat may serve as a suitable animal model to study pharmaceutical strategies for the treatment of HFpEF.